Psychological impact of an acute intervention on medical-psychological emergency unit professionals: the example of hurricane Irma. Issue 4 (14th June 2021) - Razakarivony, Oriane; Khanafer, Nagham; Philippe, Jean-Marc; Prieto, Nathalie
Abstract : Background: Medical-psychological emergency units (Cellules d'Urgence Médico-Psychologiques, CUMP) are deployed following major events where there is a risk of psychological trauma, in order to provide acute and proper psychological care for the victims. Aims: To describe and evaluate the risk of a psychological impact on CUMP professionals after their participation in the aftermath of the hurricane Irma natural disaster. CUMP teams consist of medical and paramedical staff, who can have permanent or volunteer status. We reasoned that there might be a psychological and emotional impact on CUMP professionals, despite their own expertise in the field, after their intervention following hurricane Irma. Method: A cross-sectional survey was conducted during a feedback meeting. Participating professionals completed a sociodemographic questionnaire and the Professional Quality of Life (ProQOL) scale (5th French version), which is composed of three subscales: compassion satisfaction, burnout and secondary traumatic stress (STS). Results: A total of 53 participants were included with 24 (45.3%) psychiatrists, 15 (28.3%) paramedical staff and 14 (26.4%) psychologists. The median age was 46 years (range 39–55.5) and 29 (54.7%) were women. We found that psychiatrists compared with other professions had higher secondary traumatic stress scores ( P = 0.007) and that volunteer psychiatrists had higher burnout scores than permanent psychiatrists ( P = 0.03). Conclusions: These preliminary results suggest a psychological impact attributable to leadership status, which was reserved for psychiatrists. The results also underline the need for a supportive accompaniment for such teams by promoting formation improvement, psychological support and team cohesion.